Geotechnical frontiers 2017. selected papers from sessions of Geotechnical Frontiers 2017, March 12-15, 2017, Orlando, Florida - Brandon, Thomas L.; Valentine, Richard, J. (GSP (Series) ;, 2017)
Contains 39 peer-reviewed papers on various foundation types. Topics include: bridge and offshore structures, scour, geosynthetics in foundations, offshore foundation systems, and pile, shaft and pier foundations.